Photocatalysis: Tuning the Electronic Bandgap of Graphdiyne by H‐Substitution to Promote Interfacial Charge Carrier Separation for Enhanced Photocatalytic Hydrogen Production (Adv. Funct. Mater. 29/2021). (16th July 2021) - Li, Jian; Slassi, Amine; Han, Xu; Cornil, David; Ha‐Thi, Minh‐Huong; Pino, Thomas; Debecker, Damien P.; Colbeau‐Justin, Christophe; Arbiol, Jordi; Cornil, Jérôme; Ghazzal, Mohamed Nawfal
Abstract : Tuning the electronic bandgap of graphdiyne is an efficient way to construct a type II heterojunction for photocatalysis. In article number 2100994, Mohamed Nawfal Ghazzal and co‐workers demonstrate enlarging the electronic bandgap of GDY via H‐substitution, which promotes efficient interfacial charge separation and improves photocatalytic hydrogen evolution remarkably.